Pengetahuan Ibu tentang Nutrisi pada Preschool di TK Dharma Wanita Campurejo Kediri - Diah Asriningrum (Journal of Ners and Midwifery, 2015)
Preshool is called golden age in child growth.Called golden age because there are many importan growth in this periode. Mom Knowledge about good nutrition for preschool being  importan for her to support her child optimal growh. The study purpose was to describe the knowledge of preschool mom about nutrition preshool in Campurejo Dharma Wanita Child Shool. The study used a descriptive study designe.The study population was all mom thas has  3 - 6 year of child ages. Sample taken by  purposive technique with a sample of 20 mom of preschool.The result showed that 50% responden in bad knowledge of preshcool nutrition, 30% was in midle knoledge and  20% responden in good knowledge. To increase off mom preshool nutritio knowledg,ethe goverment can give her same information about preshcool nutrition by formal or non formas class.